Pain perception and processing in individuals with posttraumatic stress disorder: a systematic review with meta-analysis - Tesarz, Jonas; Baumeister, David; Andersen, Tonny Elmose; Vaegter, Henrik Bjarke (Pain reports, 2020)
Posttraumatic stress disorder (PTSD) is a known risk factor for the development of chronic pain conditions, and almost 1 in 5 individuals with chronic pain fulfills the criteria for PTSD. However, the relationship between PTSD and pain is poorly understood and studies on pain perception in patients with PTSD show inconsistent results suggesting that different sensory profiles exist among individuals with PTSD. Here, we (1) systematically summarize the current literature on experimentally evoked pain perception in patients with PTSD compared to subjects without PTSD, and (2) assess whether the nature of the traumatic event is associated with different patterns in pain perception. The main outcome measures were pain threshold, pain tolerance, and pain intensity ratings as well as measures of temporal summation of pain and conditioned pain modulation. A systematic search of MEDLINE, EMBASE, Web of Science, PsycINFO, and CINAHL identified 21 studies for the meta-analysis, including 422 individuals with PTSD and 496 PTSD-free controls. No main effect of PTSD on any outcome measure was found. However, stratification according to the nature of trauma revealed significant differences of small to medium effect sizes. Combat-related PTSD was associated with increased pain thresholds, whereas accident-related PTSD was associated with decreased pain thresholds. No clear relationship between PTSD and experimentally evoked pain perception exists. The type of trauma may affect pain thresholds differently indicating the presence of different subgroups with qualitative differences in pain processing.